The Influence Of Human Resources Quality And Training Education On Employee Achievement: Case Study At The Population And Civil Registration Service Of Pesisir Barat District - Epi Parela; Senen Mustakim; David Ariswandy (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the effect of human resource quality and education & training on employee achievement at the Population and Civil Registration Service of Pesisir Barat District. Using a quantitative approach, the research employed a census method with 44 employees as respondents. Data were collected through structured questionnaires and analyzed with multiple regression, including validity, reliability, and classical assumption tests. The findings reveal that, simultaneously, human resource quality and education & training significantly affect employee achievement. However, partial analysis indicates that education & training exerts a stronger influence compared to human resource quality. The study contributes by highlighting the strategic role of continuous training programs in enhancing public sector performance, particularly in local government institutions in Indonesia. Theoretically, this research enriches discussions on human capital and training effectiveness, while practically, it provides recommendations for public managers to prioritize structured and sustainable training interventions. Keywords: human resource quality, education and training, employee achievement, public sector